2022
DOI: 10.3389/fonc.2022.919899
|View full text |Cite
|
Sign up to set email alerts
|

Clinical M2 Macrophage-Related Genes Can Serve as a Reliable Predictor of Lung Adenocarcinoma

Abstract: BackgroundNumerous studies have found that infiltrating M2 macrophages play an important role in the tumor progression of lung adenocarcinoma (LUAD). However, the roles of M2 macrophage infiltration and M2 macrophage-related genes in immunotherapy and clinical outcomes remain obscure.MethodsSample information was extracted from TCGA and GEO databases. The TIME landscape was revealed using the CIBERSORT algorithm. Weighted gene co-expression network analysis (WGCNA) was used to find M2 macrophage-related gene m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…We explored the association of risk signature and TMB in this study and found that risk signature and TMB had some synergistic effects in predicting patient survival. Previous studies have found that TMB can be used to predict the efficacy of immune checkpoint inhibitor therapy ( Snyder et al, 2014 ; Hugo et al, 2016 ; Carbone et al, 2017 ; Liang et al, 2021 ; Xu et al, 2022a ; Xu et al, 2022b ). It has also been found that TMB is associated with the prognosis of diffuse glioma ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We explored the association of risk signature and TMB in this study and found that risk signature and TMB had some synergistic effects in predicting patient survival. Previous studies have found that TMB can be used to predict the efficacy of immune checkpoint inhibitor therapy ( Snyder et al, 2014 ; Hugo et al, 2016 ; Carbone et al, 2017 ; Liang et al, 2021 ; Xu et al, 2022a ; Xu et al, 2022b ). It has also been found that TMB is associated with the prognosis of diffuse glioma ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used XCELL, TIMER, QUANTISEQ, MCP COUNTER, EPIC, CIBERSORT, and CIBERSORT-ABS to reveal the correlation between risk score and immune infiltrating cells ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…We used the GSVA to estimate the activity of pathways so that we could compare the activity of pathways in different samples, which are listed in the MSigDB database ( Xu et al, 2022c ).…”
Section: Methodsmentioning
confidence: 99%